Simulator Study on the Response Time and Defensive Behavior of Drivers in a Cut-in Situation - Lee, Myeongkyu; Kim, Songhui; Kim, Jonghyuk; Yang, Ji Hyun (International journal of automotive technology, 2022)
The purpose of this study was to record and analyze various reaction times and behaviors of drivers in response to cut-in situations in a driving simulator. A total of 105 male and female volunteers between the age of 20 and 49 participated in an experiment in a driving simulator with an installed eye-tracking system. The participants experienced a scenario in which a vehicle parked on a shoulder unexpectedly cut in while they were driving on a city road. The mean perceived reaction time was 1.05 s with a standard deviation of 0.43 s. The mean brake/steering reaction time after perceiving the danger was 0.59/0.56 s with a standard deviation of 0.40/0.42 s. The influence of age and gender was observed only in the steering reaction time. No interaction effects were found in any reaction times. Approximately half the drivers steered first and then braked to avoid collision. The perceived reaction time in accident cases was longer than in no-accident cases. A rich dataset was established based on the 93 valid participants who completed the experiment, and established database can be used as a look-up table to identify the percentile of a certain cut-in case.